Unraveling the celiac disease-related immunogenic complexes in a set of wheat and tritordeum genotypes: implications for low-gluten precision breeding in cereal crops - Marín-Sanz, Miriam; Barro, Francisco; Sánchez-León, Susana (Frontiers in Plant Science, 2023)
The development of low-gluten immunogenic cereal varieties is a suitable way to fight the increment of pathologies associated with the consumption of cereals. Although RNAi and CRISPR/Cas technologies were effective in providing low-gluten wheat, the regulatory framework, particularly in the European Union, is an obstacle to the short- or medium-term implementation of such lines. In the present work, we carried out a high throughput amplicon sequencing of two highly immunogenic complexes of wheat gliadins in a set of bread and durum wheat, and tritordeum genotypes. Bread wheat genotypes harboring the 1BL/1RS translocation were included in the analysis and their amplicons successfully identified. The number of CD epitopes and their abundances were determined in the alpha- and gamma-gliadin amplicons, including 40k-γ-secalin ones. Bread wheat genotypes not containing the 1BL/1RS translocation showed a higher average number of both alpha- and gamma-gliadin epitopes than those containing such translocation. Interestingly, alpha-gliadin amplicons not containing CD epitopes accounted for the highest abundance (around 53%), and the alpha- and gamma-gliadin amplicons with the highest number of epitopes were present in the D-subgenome. The durum wheat and tritordeum genotypes showed the lowest number of alpha- and gamma-gliadin CD epitopes. Our results allow progress in unraveling the immunogenic complexes of alpha- and gamma-gliadins and can contribute to the development of low-immunogenic varieties within precision breeding programs, by crossing or by CRISPR/Cas gene editing.